Knowledge, attitude and practice on hepatitis-B infection among infected patients in a Homoeopathy Medical Center in Dhaka City, Bangladesh (South East Asia Journal of Public Health, 2016)
Viral hepatitis is the commonest liver disease in Bangladesh. About 10 million people in Bangladesh have been suffering from hepatitis B. Hepatitis B is a potentiality life threatening liver infection caused by HBV. It is a major global health problem and the most serious type of viral hepatitis. The aim of this study is to assess the knowledge, attitude and practice on Hepatitis B Virus infection among the selected patients in Essence Homoeopathy Medical Center, Dhaka. A descriptive type of cross sectional study was carried out among 150 samples by using non-randomized purposive sampling technique and by the help of pretested modified questionnaire. Statistical association was calculated by chi-square test and all the Hepatitis B related data were analyzed by the help of SPSS (version 16). The study showed that 73.3% of the respondents age ranged from 15-35 years with mean age (32.44±10.54) and of them 96.7% was found to be Muslims. Among injectable drug users (IDUs) (19.3%), 27.6% was sharing same needle. Approximately 5% of the respondents had a history of taking unscreened blood among 28% of the respondents who experienced blood transfusion. Another concerning issue was that 77% of the respondents practiced polygamy sex and among them only 38.8% used protecting device during sexual activity. Majority (70.7%) of the respondents did not take HBV vaccine. Significant statistical association was found between education and vaccination against HBV (p-0.000). To prevent this deadly disease mass awareness has to be created among the people of active age group through media education and policy implementation.South East Asia Journal of Public Health Vol.6(1) 2016: 27-31